Volcanic fatalities database : analysis of volcanic threat with distance and victim classification - Brown, Sarah K. (2018)
Volcanoes can produce far-reaching hazards that extend distances of tens or hundreds of kilometres in large eruptions, or in certain conditions for smaller eruptions. About a tenth of the world’s population lives within the potential footprint of volcanic hazards and lives are regularly lost through volcanic activity: volcanic fatalities were recorded in 18 of the last 20 years. This paper identifies the distance and distribution of fatalities around volcanoes and the activities of the victims at the time of impact, sourced from an extensive search of academic and grey literature, including media and official reports. We update and expand a volcano fatality database to include all data from 1500 AD to 2017. This database contains 635 records of 278,368 fatalities. Each record contains information on the number of fatalities, fatal cause, incident date and the fatality location in terms of distance from the volcano. Distance data were previously available in just 5% of fatal incidents: these data have been significantly increased to 72% (456/635) of fatal incidents, with fatalities recorded from inside the crater to more than 100 km from the summit. Local residents are the most frequently killed, but tourists, volcanologists and members of the media are also identified as common victims. These latter groups and residents of small islands dominate the proximal fatality record up to 5 km from the volcano. Though normally accounting for small numbers of fatalities, ballistics are the most common cause of fatal incidents at this distance. Pyroclastic density currents are the dominant fatal cause at 5 to 15 km. Lahars, tsunami and tephra dominate the record after about 15 km. The new location data are used to characterise volcanic threat with distance, as a function of eruption size and hazard type, and to understand how certain activities increase exposure and the likelihood of death. These findings support assessment of volcanic threat, population exposure and vulnerabilities related to occupation or activity.